Pengaruh Dukungan Keluarga dan Pengetahuan Ibu Nifas tentang ASI Eksklusif terhadap Keberhasilan ASI Eksklusif di Puskesmas Alalak Tengah Kota Banjarmasin - Tarisa Putri; Ika Friscila; Fadhiyah Noor Anisa; Dwi Rahmawati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Based on World Health Organization (WHO) data, the global coverage of exclusive breastfeeding reached 80% in 2024. However, the success of exclusive breastfeeding is influenced by various factors, including family support and postpartum mothers’ knowledge. Exclusive breastfeeding is the primary nutritional requirement for infants during the first six months of life. Despite its importance, the coverage of exclusive breastfeeding in Indonesia remains relatively low, at 66.01% in 2024. Family support and postpartum mothers’ knowledge regarding exclusive breastfeeding are considered crucial determinants of successful exclusive breastfeeding practices. This study aimed to analyze the influence of family support and postpartum mothers’ knowledge about exclusive breastfeeding on the success of exclusive breastfeeding at Alalak Tengah Public Health Center, Banjarmasin City. This research employed a quantitative approach with a cross-sectional design. A total of 38 postpartum mothers were selected using purposive sampling. Data were analyzed using univariate and bivariate analyses with the Chi-Square test. The results showed a significant relationship between family support (p = 0.005) and maternal knowledge (p = 0.000) with the success of exclusive breastfeeding. Most mothers who had good family support and high knowledge successfully practiced exclusive breastfeeding, accounting for 28 out of 38 postpartum mothers. It can be concluded that family support and postpartum mothers’ knowledge significantly influence the success of exclusive breastfeeding.